Does market-oriented institutional change in an emerging economy make business-group-affiliated multinationals perform better? An institution-based view - Kim, Hicheon; Kim, Heechun; Hoskisson, Robert E (Journal of International Business Studies, 2010)
Viewing market-oriented institutional change as a two-staged process, we propose that the effects of market-oriented institutional change on two organizational forms – business-group-affiliated and independent firms – are different, depending on the stage of institutional change. Specifically, we examine how the two distinct periods of market-oriented institutional change – that is, institutional friction and institutional convergence – affect business-group-affiliated firms and independent firms in their abilities to profit from international diversification. Using data on 140 Korean manufacturing multinational firms from 1993 to 2003, we find that emerging-economy firms face an international diversification discount – a negative relationship between international diversification and firm performance. We also find that business group affiliation affects the international diversification discount differently during the two periods of market-oriented institutional change, particularly when firm performance is measured by the market-to-book value (MBV). The moderating effect of business group affiliation on the relationship between international diversification and MBV is negative during the institutional frictions period, but becomes positive during the institutional convergence period in the later stage of institutional change. Our findings warn against viewing market-oriented institutional change as a discrete event, highlighting the importance of recognizing the qualitatively distinctive nature of different periods of market-oriented institutional change in future research.